Unembodied Multimodal Resources in Senior High School EFL Classrooms: A Multimodal Interaction Analysis - Mhd Reza Anwar; Tien Rafida; Maslathif Dwi Purnomo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how unembodied multimodal resources construct meaning in EFL classroom interaction at the senior high school level. Grounded in Sigrid Norris's Multimodal Interaction Analysis (MIA) framework and social semiotic theory (Kress & van Leeuwen, 2001, 2006), the study investigates the meaning-constructing mechanisms through which non-bodily semiotic resources such as digital video media, projected presentation slides, physical material artifacts, and environmental spatial arrangements operate in authentic EFL instruction. Data were collected through video-recorded classroom observations of an experienced English teacher at SMA Kemala Bhayangkari, North Sumatra, Indonesia, across two classroom meetings covering procedure text and argumentative text genres. Analysis of nineteen video-captured still images reveal that meaning is constructed not through any single resource in isolation but through intermodal ensembles in which projected visual content, spoken teacher language, and embodied action converge. Five key mechanisms of meaning construction are identified: intermodal complementarity, indexical anchoring through gesture, compositional organization of projected layouts, temporal sequencing of resources, and kinesthetic affordances of physical objects. The findings demonstrate that unembodied resources serve multiple integrated pedagogical functions in EFL teaching, supporting content comprehension, enabling genre-level metalinguistic analysis, and structuring classroom participation. These results affirm the fundamentally multimodal character of EFL pedagogy and offer evidence-based implications for EFL instructional design and teacher education.